2021
DOI: 10.1161/strokeaha.120.033033
|View full text |Cite
|
Sign up to set email alerts
|

Dual Antiplatelet Therapy Versus Aspirin in Patients With Stroke or Transient Ischemic Attack: Meta-Analysis of Randomized Controlled Trials

Abstract: Background and Purpose: Antiplatelet therapy is key for preventing thrombotic events after transient ischemic attack or ischemic stroke. Although the role of aspirin is well established, there is emerging evidence for the role of short-term dual antiplatelet therapy (DAPT) in preventing recurrent stroke. Methods: We conducted a systematic review and study-level meta-analyses of randomized controlled trials comparing outcomes of early initiation of short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 12 publications
1
38
0
Order By: Relevance
“… 27 The majority of the patients were prescribed dual antiplatelets, which reflects adherence to the current recommendation of acute ischemic stroke management. 28 …”
Section: Discussionmentioning
confidence: 99%
“… 27 The majority of the patients were prescribed dual antiplatelets, which reflects adherence to the current recommendation of acute ischemic stroke management. 28 …”
Section: Discussionmentioning
confidence: 99%
“…This study is consonant with and extends prior investigations. Several trials and meta-analyses have demonstrated an advantage of short courses of DAPT over MAPT early after index event among patients with a broad range of non-cardioembolic stroke mechanisms, including large artery atherosclerosis, small vessel disease, and cryptogenic stroke ( 4 , 6 , 17 ). However, to our knowledge, this is the first meta-analysis elucidating the role of DAPT specifically in patients with symptomatic LAA.…”
Section: Discussionmentioning
confidence: 99%
“…Our search was limited to dates not included in this review (July 2020 onwards). The systematic review by Bhatia et al provided a comprehensive analysis comparing the outcomes of early initiation of short‐term dual antiplatelet therapy versus aspirin alone in patients with acute stroke or TIA [2]. The PubMed and Embase databases were systematically searched from July 2020 to 27 December 2021.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce research waste data were extracted from a recent metaanalysis of dual versus single antiplatelet therapy in acute minor ischaemic stroke or TIA [2,7]. It was considered of sufficiently high quality to avoid the need to repeat it.…”
Section: Data Sources and Search Strategymentioning
confidence: 99%
See 1 more Smart Citation